2021
DOI: 10.3389/fonc.2020.586789
|View full text |Cite
|
Sign up to set email alerts
|

Methyladenosine Modification in RNAs: Classification and Roles in Gastrointestinal Cancers

Abstract: Cellular ribonucleic acids (RNAs), including messenger RNAs (mRNAs) and non-coding RNAs (ncRNAs), harbor more than 150 forms of chemical modifications, among which methylation modifications are dynamically regulated and play significant roles in RNA metabolism. Recently, dysregulation of RNA methylation modifications is found to be linked to various physiological bioprocesses and many human diseases. Gastric cancer (GC) and colorectal cancer (CRC) are two main gastrointestinal-related cancers (GIC) and the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 175 publications
(291 reference statements)
0
36
0
Order By: Relevance
“…40 Most classifications focus on a single biological and molecular feature and in this study, a new classifier was developed by combining the hypoxic state and immune cell infiltration of gastric cancer. 41,42 Due to the complexity of immune activity and hypoxia in the tumor micro environment, few transcriptome-based biomarkers could evaluate hypoxia and immune status, so we took advantage of ssGSEA to calculate the enrichment scores of related immune and hypoxia gene sets as our evaluation index. 43,44 Of course, the gene sets of these hypoxia-related processes have been verified in GSE114083 and the results show that they can represent tumor hypoxia traits in gastric cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Most classifications focus on a single biological and molecular feature and in this study, a new classifier was developed by combining the hypoxic state and immune cell infiltration of gastric cancer. 41,42 Due to the complexity of immune activity and hypoxia in the tumor micro environment, few transcriptome-based biomarkers could evaluate hypoxia and immune status, so we took advantage of ssGSEA to calculate the enrichment scores of related immune and hypoxia gene sets as our evaluation index. 43,44 Of course, the gene sets of these hypoxia-related processes have been verified in GSE114083 and the results show that they can represent tumor hypoxia traits in gastric cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Most classifications focus on a single biological and molecular feature and in this study, a new classifier was developed by combining the hypoxic state and immune cell infiltration of gastric cancer. 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, extensive studies have shown that epigenetic alterations may occur not only at the DNA also at the RNA level, thus leading to crucial modifications in gene expression and pathway activation. In particular, dysregulation of RNA methylation (due to altered expression of specific enzymes) has been linked to the hyperactivation of the MAPK/ERK and the WNT/beta-catenin pathways in the absence of mutations of the main players of the pathway itself [26]. Finally, aberrant epigenetic regulation has been reported to occur via altered expression of members of the long non-coding RNAs (lncRNAs) family.…”
Section: Figurementioning
confidence: 99%
“…This modification is catalyzed by RNA methyltransferases known as writers, such as methyltransferase-like 14 (METTL14), and is removed by demethylases known as erasers, such as fat mass and obesity-associated protein (FTO). Additionally, m 6 A is recognized by m 6 A-binding proteins known as readers, such as IGF2BPs, which promote RNA stability and translation (2). Altogether, these proteins determine the dynamic and reversible regulation of m 6 A RNA modification (3), which can become disrupted if the expression or function of these proteins are altered, resulting in the development of human diseases and cancers (4).…”
Section: Introductionmentioning
confidence: 99%